Tracking Democracy In Islam - M. Junaidi; Sudaryono Sudaryono (Law and Justice, 2020)
This paper aims to answer the question “Is democracy in conflict with Islam?” This paper also discusses the values contained in democracy. This paper uses a normative legal research method that is descriptive and analytic to describe the implementation of government systems and political systems in Islam. Then analyze it with democratic values as a system of government and a political system. The research results obtained a brief description of democracy as a political system and government system in the era of the Prophet and the era of Khulafaturrasyidin to determine the democratic values contained. In the end, this paper is one of the answers to the discourse that has been a growing polemic between democracy and Islam.